The Berenstain's "B" Book - Stan & Jan Berenstain (New York, United States Random House, 1971)
In the B Book, the youngest child will be entertained by a hilarious build-up of words beginning with the letter B. It's an ideal introduction to the realisation that letters represent sounds, and end with a bang! Ages 3+
Keywords: Read Aloud -- Read Aloud